2017
DOI: 10.1039/c6ee03748h
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose fermentation and residual solids characterization for senescent switchgrass fermentation by Clostridium thermocellum in the presence and absence of continuous in situ ball-milling

Abstract: Milling during lignocellulosic fermentation, cotreatment, is investigated as an alternative to thermochemical pretreatment for biological processing of cellulosic biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…While not yet completely understood, the effectiveness of C. thermocellum at lignocellulose solubilization has been attributed to the ability to splay ends of cellulose fibers [21] and the presence of multiple cellulase modalities [22 ]. C. thermocellum has also been shown to be capable of carrying out soluble sugar fermentation in the presence of aggressive ball milling, whereas yeast has not [23]. Wildtype strains of C. thermocellum and other thermophilic, saccharolytic anaerobes produce organic acids, in particular acetic acid, in addition to ethanol and do not exhibit high ethanol tolerance.…”
Section: An Illustrative Examplementioning
confidence: 99%
“…While not yet completely understood, the effectiveness of C. thermocellum at lignocellulose solubilization has been attributed to the ability to splay ends of cellulose fibers [21] and the presence of multiple cellulase modalities [22 ]. C. thermocellum has also been shown to be capable of carrying out soluble sugar fermentation in the presence of aggressive ball milling, whereas yeast has not [23]. Wildtype strains of C. thermocellum and other thermophilic, saccharolytic anaerobes produce organic acids, in particular acetic acid, in addition to ethanol and do not exhibit high ethanol tolerance.…”
Section: An Illustrative Examplementioning
confidence: 99%
“…Inspired by the positive effect of rumination on feed digestibility, Balch et al (2017) investigated the impact of continuous ball milling on the solubilization of senescent switchgrass in fermentations by C. thermocellum. The authors demonstrated that the total carbohydrate solubilization could be increased from 45% without ball milling to 88% by in situ ball milling.…”
Section: Fundamental Investigations On Defined Anaerobic Cellulolyticmentioning
confidence: 99%
“…5 Biomass modification is essential through either physical/chemical pretreatment or cotreatment of biomass to achieve high solubilization of polysaccharides by biological systems. [6][7][8][9][10][11] For ethanol production via a biological route, enzymatic hydrolysis of cellulose is a heterogeneous reaction in which enzymes derived from † These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%